Penerapan produksi bersih pada industri pengolahan terasi skala rumah tangga di Dusun Selangan Laut Pesisir Bontang: Application cleaner production options on fermented shrimp processing industry in household scale in Selangan Laut, Bontang Waters - Mohamad Ma’ruf; Komsanah Sukarti; Elly Purnamasari; Erwan Sulistianto (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2022)
The purpose of this study is to describe the actual activities of fisherwomen at Selangan Laut that produce shrimp paste. In addition to analyzing the feasibility of their business. Further study of cleaner production options that can be applied in the processing activities to be more effective in terms of cost, time and energy and environmental friendly. Data were collected through interviews and observation techniques participate, then analyzed descriptively by tabulation and flow charts include financial analysis. Results showed financially fermented shrimp processing business conducted by the wives of the fishermen to be developed because the investment criteria NPV USD 29149.80> 0, the value of IRR 35%> 10% OCC, 1.23 times Net BCR> 1 time and Payback period of 2.98 years. In the processing of shrimp paste can still be improved efficiency and hygiene. Efforts that can be done is to make the SOP (standard operating procedure) processing shrimp paste, provides storage of raw materials and the layout of the equipment used. In terms of promotions and marketing seeks to follow events / fairs food industry, analyzing the nutritional value as well as providing content in the form of certified halal label, expiration date and composition of nutrients that are safe for consumption and widely known.